Multimodal Intermediate Tasks for Zero-Shot Cross-Lingual Transfer on XTREME-R - Assignee Research (Assignee Research, 2026)
There has been a recent spike in interest in multi-modal Language and Vision problems. On the language side, most of these models primarily focus on English since most multi-modal datasets are monolingual. We try to bridge this gap with a zero-shot approach for learning multi-modal representations using cross-lingual pre-training on the text side. We present a simple yet practical approach for building a cross-lingual image retrieval model which trains on a monolingual training dataset but can b
Machine-generated literature synthesis.